Applications and Future Prospects of Proteases: An Overview (International Journal of Food and Nutritional Sciences, 2022)
Proteases are enzymes with highly specialized proteolytic functions. Proteases are classified ashighly demanded enzymes with numerous plant, animal, and microbial sources. They are presentin all living things and are crucial for the development and differentiation of cells. They not onlyhave several physiological functions and roles in living beings but are also of great importance invarious industries as well thus providing a lot of economic benefits. This review aims to studyand analyze the updated information on various biological aspects of proteases highlighting theirsources, types, and mode of actionon microbial production of the enzyme and their industrialapplications.